Minat Siswa dalam Mengikuti Ekstrakurikuler Olahraga di SMA Negeri 20 Kabupaten Tangerang - Nurmawati Nurmawati; Citra Resita; Rolly Afrinaldi (Universitas Singaperbangsa, 2020)
This research aims to know how interested students are in following an extracurricular sport in SMA Negeri 20 Tangerang Regency. The instrument used is a poll using the Alpha Crobach 0.946 formula in SPSS 22.0 for Windows program. The results of the study are likely to be in a medium category with a low category of 13.75%, Medium category 58.75%, and category height 27.5%.